2019
DOI: 10.1007/s11663-019-01578-0
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Wetting Between Liquid Copper and Solid Steel: A Simple Extraction Technique

Abstract: Copper contamination of end-of-life steel scrap is the main barrier to high-quality recycling. Preferential melting of copper from solid steel scrap is a potential extraction technique, which could be integrated into conventional scrap re-melting with little additional energy. However, previous investigations show removal of liquid copper is limited by its adherence to solid scrap. Preventing wetting between liquid copper and steel is essential to enable separation. The carbon content of steel, initial surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Once the copper has melted and formed the droplet, in the case of the copper-EUROFER system, it tends to expand over the EUROFER substrate, covering a large surface area. This behavior is a result of the excellent wettability of copper in steel, a phenomenon that has been extensively studied in plain steel by several authors [21][22][23]. During the initial moments of the melting process, the expansion reaches up to 400% of the initial area.…”
Section: Wetting Angle Measurements Of Cu Braze On Tungsten and Eurofermentioning
confidence: 91%
“…Once the copper has melted and formed the droplet, in the case of the copper-EUROFER system, it tends to expand over the EUROFER substrate, covering a large surface area. This behavior is a result of the excellent wettability of copper in steel, a phenomenon that has been extensively studied in plain steel by several authors [21][22][23]. During the initial moments of the melting process, the expansion reaches up to 400% of the initial area.…”
Section: Wetting Angle Measurements Of Cu Braze On Tungsten and Eurofermentioning
confidence: 91%
“…In this study, for copper surface coating, the super-spread wettability properties of liquid copper are exploited. The literature reports that liquid copper is not able to wet a solid oxide [ 33 , 34 ]. However, our previous works have shown that liquid copper unusually penetrates and spreads on a surface with fine crevice structures formed by capillary action [ 35 ].…”
Section: Introductionmentioning
confidence: 99%